Corporate investment trends in Germany: The role of financialization, intangibles and M&A - Carmen Giovanazzi; Vincent Victor; Dorothee Putscher (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
We examine the dynamics of corporate investment in Germany during the 2000s, a period marked by stagnant macroeconomic investment spending. Employing a mixed-methods approach, we explore investment trends across national accounts data, firm-level financials, and responses from financial executives through our financial strategy survey. We show that while tangible investment remains the most important investment category, both macroeconomic and firm-level data indicate a decline. This decrease is offset by rising intangible investment, reflecting the emergence of the intangible economy. Despite this shift, investment has lagged behind rising corporate saving, leading to an increased net lending position. Often interpreted as corporate financialization, we find only moderate and partial evidence to support this view from a firm-level perspective. Additionally, while we find an increasing importance of M&A at the firm level, this development is not fully captured in the national accounts due to missing goodwill data. Our results underscore the necessity of multifaceted analysis in understanding investment dynamics.
Keywords: C83; D22; E01; E22; G3; L2; 330; CFO Survey; Intangible Economy; Investment Strategy; Germany; M&A; Mixed Methods; Financialization